Fourier transform infrared (FTIR) spectroscopy - Mohamed, M. A. (Elsevier Inc., 2017)
The use of Fourier transform infrared (FTIR) spectroscopy has been considered to be one of the most effective techniques to study and understand the chemical and surface chemistry in various types of membrane. In this chapter, the role of FTIR techniques to monitor the change of membrane surface chemistry was discussed. Without knowing the specific functional group, which had altered the membrane surface behavior, the researcher is unable to explain different physicochemical properties that significantly changed the membrane performance. In addition, the FTIR techniques can also be used to monitor the stability and durability of the specific membrane toward their performance. In general, the use of FTIR analysis in the field of membrane application is crucial to support the justification of the changes in their properties and performance in various applications.